Metabolic effects of antihypertensive medications: prognostic role in the development of cardiovascular disease and diabetes mellitus - M. V. Stroeva; M. N. Mamedov (Кардиоваскулярная терапия и профилактика, 2010)
Recently, more and more attention has been paid to metabolic risk factors (RFs), due to their prognostic importance in the development of cardiovascular disease (CVD) and Type 2 diabetes mellitus. The metabolic effects of antihypertensive medications are actively discussed in the literature. It has been demonstrated that ACE inhibitors, calcium antagonists, and I1-imidasoline receptor agonists (IRA) do not affect metabolic RFs, while diuretics (D) and beta-adrenoblockers could worsen the prognosis. In the new European guidelines, alpha-adrenoblockers and IRA are not regarded as first-choice medications, due to the lacking evidence of their effects on end-points. The paper analyses in detail the results of large-scale international trials on D. In particular, the authors discuss the potential of low-dose thiazide D, as a part of combined therapy, in patients with metabolic disturbances and high cardiovascular risk.